The public relations handbook - Theaker, Alison (Media practice., 2016)
"The Public Relations Handbook, Fifth Edition provides an engaging overview and in-depth exploration of a dynamic and ever evolving industry. The diverse chapters are united by a set of student friendly features throughout, including clear chapter aims, analytical discussion questions, and key further reading. Featuring wide ranging contributions from key figures in the PR profession, the new edition presents a new chapter on public relations and activism, alongside discussion of key critical themes in public relations research and exploratory case studies on public relations practices in relation to a variety of different institutions, including The Bank of Scotland, Queen Margaret University, Diabetes UK, Continental Tyres, and Action for Children."--Provided by publisher